Sistem Presensi Perkuliahan Berbasis Radio Frequency Identification - Dr. Iswanjono; Nana Natalianto (Media Teknika, 2017)
In general, the present attendance system is using a paper file containing the signature column of the participating students and lecturers of the course. The problem that arises is the presence of signature due to the student's absence. Students in one sem ester must attend lectures as much as 75% of meetings held lecturers as the requirement to take the final exam of the semester. Student attendance calculations take a relatively long time for each course. For that in this research made cource attendance system based on radio frequency identification (RFID) and fingerprint. As RFID card used e -ID card. The result showed that the maximum e-KTP card reading distance of 2 cm and fingerprint ID reading with time between 1.945 to 2.227 seconds. The success rate of reading e-KTP card and fingerprint ID is 100%. The overall test of attendance system shows 100% success rate. Presence data is displayed in the GUI and stored in database and exported in .xls format.Keywords: RFID, Fingerprint, Presence, Visual Basic 6.0, MySQL, Arduino Mega 2560